The History of Muslims and Christians in Papua: Tracing Cultural and Religious Heritage - Cahyo Pamungkas (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This is article derived from a thesis study in the Sociology Department of the University of Indonesia in 2008 exploring socio-economic, socio-political and socio-cultural contexts playing their roles in the formation of the political and religious fields along with their respective ‘habitus’ of the social agents in the Papua land. This paper discusses the history of the term “papua” itself based on a historical study conducted by Solewijn Gelpke (1993). Based on historical approach, the relationship between Muslims and Christians in Papua can be traced as a religious and cultural heritage. Also, by using a sociological conception elaborated by Bourdieu (1992: 9), we may view the Papua land as a social space encompassing all conceptions of the social world. Bourdieu’s social space conception considers the social reality as a topology (Harker, 1990).